Agreement of adolescents' self-perception of their body image with the analysis on the three-dimensional body image - Susana Cararo Confortin; Camila Meireles Souza; Bianca Rodrigues de Oliveira; Karla Daniele Silva Marques; Lívia Carolina Sobrinho Rudakoff; Elma Izze da Silva Magalhães; Antônio Augusto Moura da Silva (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to verify the agreement among adolescents' perception of their own body image and the health professionals' analysis based on three-dimensional body image and the inter-rater agreement. Methods: a cross-sectional study was carried out with 1,662 adolescents, aged 18 to 19 years old, from the 1997/98 birth cohort in São Luís, Maranhão. Self-perception of body image was assessed using the Stunkard's body image scale. Three nutritionists evaluated the three-dimensional body image obtained by the Photonic Scanner (3D Body Scanner) and classified according to the Stunkard's scale. The agreement between raters was verified by using weighted Kappa. Results: the analysis of agreement between raters in the general group and when stratified by sexwas considered moderate to good by Kappa. Regarding the intraclass correlation (ICC), good and excellent correlation values were observed both in the general group, males and females. There was a greater perception of overweight by all raters, when compared with the adolescents' self-assessments. When stratified by sex, examiner 1 had the same perception as male self-assessments, as for females the perception of overweight was more frequent, as well as raters 2 and 3, for both sexes. Conclusion: agreement between raters and self-assessments was considered weak/moderate in Kappa and good/excellent in ICC.